Analisis Bibliometrik: Strategic Management dan Firms’ Performance di SME - Frisqha Sekar G. C. Lintang; Muhammad Saiful Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Strategic management is the essential basis for supporting the success of an organisation. Strategi management play its role in making the right decision. Strategic management affects the performance of a company, especially small and medium-sized enterprise (SME). This study conducted a systematic literature review and bibliometric analysis by collecting 104 relevant articles. The bibliometric findings indicate that the trend of strategic management research on small-medium enterprise performance has increased from 1989 to 2022. The results of the regional contributions analysis show that the United Kingdom, United States, and Canada were the dominant countries in this research field. The content analysis identified major themes and research trends in this field, including innovation, dynamic capability, strategic choice, RBV, entrepreneurship, customer orientation, and strategic human resource management. Finally, the findings present research gaps, as well as recommendation to examine the influence of resource-based view on industrial organizations.